The New Role of AMP-Activated Protein Kinase in Regulating Fat Metabolism and Energy Expenditure in Adipose Tissue - Qun Wang; Jiayi Sun; Mengyu Liu; Yaqi Zhou; Lei Zhang; Yanzhang Li (Biomolecules, 2021)
Obesity is characterized by excessive accumulation of fat in the body, which is triggered by a body energy intake larger than body energy consumption. Due to complications such as cardiovascular diseases, type 2 diabetes (T2DM), obstructive pneumonia and arthritis, as well as high mortality, morbidity and economic cost, obesity has become a major health problem. The global prevalence of obesity, and its comorbidities is escalating at alarming rates, demanding the development of additional classes of therapeutics to reduce the burden of disease further. As a central energy sensor, the AMP-activated protein kinase (AMPK) has recently been elucidated to play a paramount role in fat synthesis and catabolism, especially in regulating the energy expenditure of brown/beige adipose tissue and the browning of white adipose tissue (WAT). This review discussed the role of AMPK in fat metabolism in adipose tissue, emphasizing its role in the energy expenditure of brown/beige adipose tissue and browning of WAT. A deeper understanding of the role of AMPK in regulating fat metabolism and energy expenditure can provide new insights into obesity research and treatment.